Experimental and Numerical Analysis of Photovoltaics System Improvements in Urban Area = Eksperymentalna i numeryczna analiza usprawnień systemu fotowoltaicznego w terenie miejskim - Żołądek, Maciej; Sornek, Krzysztof; Papis, Karolina; Figaj, Rafał; Filipowicz, Mariusz (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Nowadays, photovoltaic systems installed in urban areas have to be an essential part of distributed generation systems, and lead to improve energy efficiency of buildings. The paper describes the operation aspects of the 7,5 kWp photovoltaic installation located on the roof of the didactic building of AGH University of Science and Technology.
Keywords: renewable energy sources; solar energy; sun-tracking devices; TRNSYS; dynamic simulation; odnawialne źródła energii; energia słoneczna; systemy nadążne; symulacja dynamiczna